Puan Norlis's retirement day / Nor Ashikin Sahrom - Sahrom, Nor Ashikin (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
The UiTM staff retirement programme, everyone has to deal with retirement day, and it is the time for our lovely colleague, Puan Norlis Osman, one of the senior lecturers in the Faculty of Computer and Mathematical The event was held for almost 3 hours, starts with Dua' recitation from Miss Intan Syaherra and the welcoming speech from the emcee, Puan Zuraida. Then, it continued with a warm speech from Coordinator, Puan Siti Nur Dina Ahmad. Sciences (FSKM). The event was held on 24th March 2021 at the Royale Chulan Hotel, Seremban which involved all the FSKM lecturers to honor and spend time together with our beloved "idol". Puan Norlis is known as a person who always motivate and inspire the younger colleagues. She is very energetic and willing to help each person in this faculty and yet to UiTM Cawangan Negeri Sembilan staff as well.